2004
DOI: 10.1007/s00216-003-2369-0
|View full text |Cite
|
Sign up to set email alerts
|

Current strategies for electrochemical detection of DNA with solid electrodes

Abstract: A review of current strategies aimed at detecting nucleic acids (NA) using NA-modified solid electrodes reveals the versatility and potential of electrochemical detection in this field. What emerged at the beginning of 90s as a very promising detection system in DNA technology is now resulting in the first commercial devices. Many aspects of the experimental design, for example surface immobilisation and detection schemes, are outlined and evaluated. Although most approaches use hybridisation as the recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 183 publications
(260 reference statements)
4
64
0
1
Order By: Relevance
“…This hypothesis is supported by the fact that the E 0 ' of the redox couple (II) agree with those obtained from other N9 substituted adenine parent compounds [11]. Although no chlorine atom could be electrochemically measured, we detected bromine and fluorine atoms after the oxidation of 2-bromo-cicloAMP [11] and fludarabine [18] respectively, which suggested that it is reasonable to think that chlorine atom can also be eliminated from the pyrimidine ring. That elimination has already been proposed for 2-bromo-2'-deoxyadenosine [16].…”
supporting
confidence: 71%
“…This hypothesis is supported by the fact that the E 0 ' of the redox couple (II) agree with those obtained from other N9 substituted adenine parent compounds [11]. Although no chlorine atom could be electrochemically measured, we detected bromine and fluorine atoms after the oxidation of 2-bromo-cicloAMP [11] and fludarabine [18] respectively, which suggested that it is reasonable to think that chlorine atom can also be eliminated from the pyrimidine ring. That elimination has already been proposed for 2-bromo-2'-deoxyadenosine [16].…”
supporting
confidence: 71%
“…Although it is possible to carry out the selection of the aptamer (SELEX) using labeled oligonucleotides libraries to ensure the perfect binding of the aptamer selected to the analyte [92], label-free methods are highly desirable and are experiencing an important development with improved sensitivity [62].…”
Section: Label-free Methodsmentioning
confidence: 99%
“…Since then, an exponential number of electrochemical devices have appeared. The discussion will be focused on the latest improvements that have not been covered in previous reviews [61,62,65].…”
Section: Aptamer-based Sensorsmentioning
confidence: 99%
“…This catalytic activity was attributed to the 2,8-dioxoadenine derivative with quinoneimine structure, generated after the electrochemical oxidation of the adenine moiety in the molecule. This structure is stabilized from nucleophilic attack by the bulk substituent in N9 position of the adenine [2].…”
Section: Introductionmentioning
confidence: 97%